In Situ Chemical Probing of Vacancy Defects in Graphene and Boron Nitride at Room Temperature - (:unkn) unknown (My University, 2019)
IN SITU CHEMICAL PROBING OF VACANCY DEFECTS IN GRAPHENE AND BORON NITRIDE AT ROOM TEMPERATURE by Ali Ihsan Altan The University of Wisconsin-Milwaukee, 2019 Under the Supervision of Professor Jian Chen Chemical vapor deposition (CVD) has emerged as the most promising technique towards manufacturing of large area, high quality graphene. Characterization, understanding, and controlling of various structural defects in CVD-grown graphene are essential to realize its true potential for real-world applications. We report a new method for in situ chemical probing of vacancy defects in CVD-grown graphene at room temperature. Our approach is based on a solid–gas phase reaction that occurs selectively in graphene vacancy defect regions such as holes and cracks. Our new probing technique has a unique combination of the following advantages: (1) no exposure to liquids; (2) non-damaging in situ probing; (3) high selectivity, sensitivity, and reliability towards vacancy defects; (4) simplicity and scalability. By focusing on hexagonal graphene domains, we have made the following findings: (1) the nucleation centers of graphene domains are favorable locations of hole defects. (2) The lengthy electron-beam irradiation at very low energy (3.5 keV) could etch the graphene. (3) Graphene cracks often kink at the angle of primarily 150° or 120°. (4) There exist complex graphene cracks such as cracks with clock-hands patterns, and cracks with snowflake-like branched structures. (5) There exist discontinuous cracks in some graphene domains, where hole defects are oriented along a straight or curved line. Such discontinuous cracks may arise from the ductile fracture of graphene. In addition, we have shown that our method is also applicable to chemical probing of vacancy defects such as holes, continuous and discontinuous cracks in CVD-grown monolayer polycrystalline graphene films on copper. Our study also suggests that the copper grain and copper grain boundary play significant roles in formation and distribution of graphene vacancy defects. We have studied and clarified potential effects of graphene wrinkles on the formation of vacancy defects in polycrystalline graphene and single crystalline graphene, respectively. We have found that although the graphene wrinkles are the main source for vacancy defects in the polycrystalline CVD-grown graphene samples, there are other possible sources such as mechanical stress that are responsible for the formation of vacancy defects in polycrystalline graphene where wrinkles are not found. In contrast, we have found that graphene wrinkles are NOT mainly responsible for the observed vacancy defects in single crystalline hexagonal graphene domains, which provides further indirect support that the copper grain and copper grain boundary play significant roles in formation and distribution of graphene vacancy defects, and the observed discontinuous cracks more likely originate from a ductile fracture of graphene. The practical investigation of individual nanoscale vacancy defects in h-BN still remains a great challenge. Hence, it is important to develop a method for rapidly identification of the vacancy defects in large area monolayer h-BN, which will provide insightful information on defect formation in h-BN. We have performed in situ chemical probing study of vacancy defects in CVD-grown h-BN. Our H2S gas treatment procedure reveals that currently commercially available CVD-grown monolayer h-BN samples have high density of nanoscale voids. High defect density in monolayer h-BN appears to be caused by the hardship of stitching of individual domains with various rotations and edge atoms. It has been shown that h-BN may have nanoscale vacancy defects along the grain boundaries which is different than graphene. It is important to limit H2S amount and treatment time for our method to work well towards identification of vacancies.
Keywords: boron nitride; CVD; graphene; graphene crack; hole defect; vacancy defect